2011
DOI: 10.1007/s00404-011-1881-2
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous administration of mifepristone and misoprostol for early termination of pregnancy: a randomized controlled trial

Abstract: Simultaneous administration of mifepristone and 400 μg vaginal misoprostol is an effective alternative to standard regimens for medical abortion up to 49 days of gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 20 publications
3
31
0
Order By: Relevance
“…[7][8][9][10][11][12] Overall it has been shown that an interval of approximately 6 hours between mifepristone and misoprostol results in equal efficacy as 24-48 hours in first-trimester abortion. There have been several studies specifically assessing the interval between mifepristone and misoprostol administration with respect to abortion outcome.…”
Section: Methods Of Study Selectionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Overall it has been shown that an interval of approximately 6 hours between mifepristone and misoprostol results in equal efficacy as 24-48 hours in first-trimester abortion. There have been several studies specifically assessing the interval between mifepristone and misoprostol administration with respect to abortion outcome.…”
Section: Methods Of Study Selectionmentioning
confidence: 99%
“…There may be little to no difference in rates of successful abortion between concurrent administration of misoprostol and a 24-hour interval (RR 1.01 CI 95% 0.84-1.21, very low certainty of evidence) [23,24]. There was no signi cant difference between 24-hour and 48-hour interval in terms of ongoing pregnancy and successful abortion [10,21,22].…”
Section: Comparison Of Dosing Intervals Between Mifepristone and Misomentioning
confidence: 99%
“…Eight studies assessed different time intervals between mifepristone and misoprostol dosing in the combined regimen. These include comparisons between < 8 hours vs. > 24 hours [8,9], 24 hours vs. 48 hours [10,21,22], concurrent administration vs. 24 hours [23,24] and < 8 hours vs. 48 hours [25] (Table 2).…”
Section: Comparison Of Dosing Intervals Between Mifepristone and Misomentioning
confidence: 99%
“…Ashok et al (1998) reported a success rate of 99.4% in 2000 women. Alternatives to the 48 hour interval are immediate with no interval, or a 24-36 hour interval; although the success rates for these are lower they are still in the high nineties (Goel et al, 2011). The highest success rates for stimulating expulsive uterine contractions are with the woman, after washing her hands and wetting the tablets with a quick dip in water, inserting the four misoprostol 200 mcg tablets vaginally.…”
Section: Induction With Mifepristone and Misoprostolmentioning
confidence: 99%